Measurement of the muon stopping power in lead tungstate - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Adam, W; Arnold, B; Bergauer, H; Bergauer, T; Dragicevic, M; Eichberger, M; Erö, J; Friedl, M; Frühwirth, R; et al. (2010)
A large sample of cosmic ray events collected by the CMS detector is exploited to measure the specific energy loss of muons in the lead tungstate (PbWO4) of the electromagnetic calorimeter. The measurement spans a momentum range from 5 GeV/c to 1 TeV/c. The results are consistent with the expectations over the entire range. The calorimeter energy scale, set with 120 GeV/c electrons, is validated down to the sub-GeV region using energy deposits, of order 100 MeV, associated with low-momentum muons. The muon critical energy in PbWO4 is measured to be 160+5-68 GeV, in agreement with expectations. This is the first experimental determination of muon critical energy. © 2010 IOP Publishing Ltd and SISSA.